A facile microwave-assisted synthesis of PbMoO4 nanoparticles and their key characteristics analysis: a good contender for photocatalytic applications. (17th August 2018) - Shkir, Mohd; Khan, Z R; Hamdy, M S; Algarni, H; AlFaify, S
Abstract: This work reports the synthesis of lead molybdate (PMO) nanoparticles via simple facile microwave assisted method and their characterization. The prepared product was characterized using different characterization techniques such as x-ray diffraction, FT-Raman, SEM, UV–vis spectrophotometer. Also, the dielectric and electrical properties of synthesized nanoparticles studied by electrical characterization unit. The grown nanoparticles showed the scheelite type tetragonal structure along (112) plane with single phase and space group I41 /a. Raman spectrum of grown PMO nanoparticles shows 6 vibrational peaks which confirm the formation of structurally ordered material. Absorbance spectra shows high absorbance in visible region and value of direct and indirect band gaps are estimated to be ∼2.87 and 2.69 eV, respectively. Dielectric constant and loss is decreases with increase in frequency. The ac conductivity increases with the increase in frequency. The photocatalytic activity of the prepared sample was investigated in decolourization reaction of methyl green as a model compound under the illumination of visible light. Results show that PMO is a promising photocatalyst compared to the commercially available semiconductors and the photocatalytic activity is about 12 times higher than commercial semiconductors.